Pengaruh Penggunaan Tepung Sorgum Putih (Sorgum bicolor L. Moench) sebagai Pengganti Tapioka terhadap Sifat Fisikkimia dan Sifat Organoleptik Bakso Itik Manila (Cairina Moschata): Effect of the Usingof White Sorgum (Sorghum bicolor L. Moench) Flour as A Substitute for Tapioca Flour on Physicochemical and Organoleptic Properties of Manila Duck Meats (Cairina Moschata) - Oktaviana Raflesiana Isaberta Bere; Geertruida Margareth Sipahelut; Heri Armadianto (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of using white sorghum flour as a substitute for tapioca flour on water content, protein content, amylose, elasticity, color and taste of manila duck meatballs. This research uses Completely Randomized Design (CRD) with 5 treatments consisted of (P0 = 0% white sorghum flour + 40% tapioca flour, P1 = 10% white sorghum flour + 30% tapioca flour, P2 = 20% white sorghum flour + 20% tapioca flour, P3 = 30% white sorghum flour + 20% tapioca flour, P4 = 40% white sorghum flour). Each treatment was repeated 3 times so that there were 15 experimental units. The results of the analysis showed that the addition of white sorghum flour levels up to 40% could affect the protein, amylose, taste and color content (P<0.05), while the moisture content and elasticity had nosignificant effect (P>0.05). In conclusion, the use of sorghum flour up to 40% did not affect the moisture content and elasticity but did affect the protein content, amylose, taste and color. Amylose content and elasticity decreased with increasing level of use of sorghum flour, while color and taste variations occurred in assessment. In conclusion, the use of 10%(100 gr) sorghum flour + 30%(300 gr) tapioca flour is still favored by the panelist. Tujuan penelitian ini yaitu untuk mengetahui pengaruh penggunaan tepung sorgum putih sebagai pengganti tapioka terhadap kadar air, kadar protein, amilosa, kekenyalan, warna dan rasa bakso itik manila (Cairina Moschata) . Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari 5 perlakuan yaitu (P0= 0% tepung sorgum putih +40% tepung tapioka, P1=10% tepung sorgum putih + 30% tepung tapioka, P2= 20%tepung sorgum putih + 20% tepung tapioka, P3= 30% tepung sorgum putih + 20% tepung tapioka, P4= 40% tepung sorgum putih). Setiap perlakuan diulang sebanyak 3 kali ulangan sehingga terdapat 15 unit percobaan. Hasil analisis menunjukkan bahwa penambahan level tepung sorgum putih hingga 40% dapat mempengaruhi kadar protein, amilosa, rasa dan warna (P<0.05), sedangkan kadar air dan kekenyalan tidak berpengaruh nyata (P>0,05). Kesimpulan, penggunaan tepung sorgum hingga 40% tidak mempengaruhi kadar air dan kekenyalan namun memberikan pengaruh terhadap kadar protein, amilosa, rasa dan warna. Kadar amilosa dan kekenyalan menurun seiring bertambahnya level penggunaan tepung sorgum sedangkan warna dan rasa terjadi variasi penilaian. Penggunaan tepung sorgum 10% (100 gr) + tepung tapioka 30% (300 gr masih disukai oleh panelis.